2019
DOI: 10.1038/s41581-019-0131-x
|View full text |Cite
|
Sign up to set email alerts
|

The adjuvant treatment of kidney cancer: a multidisciplinary outlook

Abstract: Among patients who undergo surgery for these cancers, 30-35% will eventually develop potentially fatal metachronous distant metastases. Effective adjuvant treatments are urgently needed to reduce the risk of recurrence of kidney cancer and of dying of metastatic disease. To date, almost all of the tested adjuvant agents have failed to demonstrate any benefit. Only two trials of an autologous renal tumour cell vaccine and of the VEGFR tyrosine kinase inhibitor sunitinib have shown positive results but these hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 67 publications
(51 reference statements)
0
53
0
1
Order By: Relevance
“…Intriguingly, TOC significantly increased the TTP for dogs suffering from SBA, LA, and RCC, and some advanced types of adenocarcinomas that had higher mitotic index, invasive characteristics, and lymph node metastases. Several studies have reported that postoperative adjuvant treatment with sunitinib and sorafenib was efficacious in human patients with advanced RCC 22‐24 . Reports in the veterinary literature also have indicated that postoperative adjuvant treatment may improve survival time in dogs with SBA 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, TOC significantly increased the TTP for dogs suffering from SBA, LA, and RCC, and some advanced types of adenocarcinomas that had higher mitotic index, invasive characteristics, and lymph node metastases. Several studies have reported that postoperative adjuvant treatment with sunitinib and sorafenib was efficacious in human patients with advanced RCC 22‐24 . Reports in the veterinary literature also have indicated that postoperative adjuvant treatment may improve survival time in dogs with SBA 25 .…”
Section: Discussionmentioning
confidence: 99%
“…More than 10 histological and molecular subtypes of RCC have been identified, among which clear cell RCC (ccRCC) is the most common type and accounting for 80% of all cases 2 , 4 . The prognosis of RCC is poor because approximately 25% of patients present with metastases at the time of diagnosis, and another 30-35% of patients underwent resection for localized or locally invasive kidney cancer will develop potentially fatal metachronous distant metastases 5 , 6 . Therefore, a comprehensive understanding of RCC metastasis is urgently needed to develop effective targeted therapies for reducing the risk of recurrence and death from metastatic disease.…”
Section: Introductionmentioning
confidence: 99%
“…RCC is the malignant tumor with the highest mortality rate in the urogenital system. Over the past decade, there has been some progress in the treatment of RCC, such as the advent of targeted agents and immune checkpoint inhibitors [ 27 ]; however, the clinical outcomes of patients with RCC are still unsatisfactory [ 28 , 29 ]. Hence, it is necessary to identify new biomarkers that provide valuable information for clinicians to choose appropriate treatment options and predict prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%